2017
DOI: 10.1117/1.jmi.4.4.041304
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning in breast cancer risk assessment: evaluation of convolutional neural networks on a clinical dataset of full-field digital mammograms

Abstract: To evaluate deep learning in the assessment of breast cancer risk in which convolutional neural networks (CNNs) with transfer learning are used to extract parenchymal characteristics directly from full-field digital mammographic (FFDM) images instead of using computerized radiographic texture analysis (RTA), 456 clinical FFDM cases were included: a "high-risk" BRCA1/2 gene-mutation carriers dataset (53 cases), a "high-risk" unilateral cancer patients dataset (75 cases), and a "low-risk dataset" (328 cases). De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 43 publications
1
63
0
1
Order By: Relevance
“…Advances in both imaging and computers have synergistically led to a rapid rise in the potential use of AI in various tasks in breast imaging, such as risk assessment, detection, diagnosis, prognosis, and response to therapy (Table ) …”
Section: Breast Cancer Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances in both imaging and computers have synergistically led to a rapid rise in the potential use of AI in various tasks in breast imaging, such as risk assessment, detection, diagnosis, prognosis, and response to therapy (Table ) …”
Section: Breast Cancer Imagingmentioning
confidence: 99%
“…By using radiomic texture analysis, investigators have characterized the spatial distribution of the gray‐scale levels within regions on FFDM when a skewness measure was incorporated into the analysis of mammograms to describe the density variation . Others have used texture analysis and deep learning to discriminate BRCA1/BRCA2 gene mutation carriers (or women with breast cancer in the contralateral breast) from women at low risk of breast cancer and, using almost 500 cases, found that women at high risk of breast cancer have dense breasts with parenchymal patterns that are coarse and low in contrast (AUC, approximately 0.82) . Further efforts have applied texture analysis to breast tomosynthesis images to characterize the parenchyma pattern for ultimate use in breast cancer risk estimation, with preliminary results indicating that texture features correlated better with breast density on breast tomosynthesis ( P = .003 in regression analysis) than on digital mammograms …”
Section: Breast Cancer Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“… (a) Schematic diagram of radiomic texture analysis (RTA) and deep CNN‐based methods for breast cancer risk assessment (Ref. ). (b) Scatterplots show distributions of 60 low‐risk cases and 30 BRCA1 and BRCA2 mutation carriers in an age‐matched group in terms of radiomic features of (a) skewness vs. coarseness and (b) coarseness vs. contrast.…”
Section: Risk Assessment and Preventionmentioning
confidence: 99%
“…Deep learning methods, such as convolution neural networks (CNNs), have been widely used in image segmentation, object classification and recognition [9][10][11] and are now being adapted in biomedical image analysis to facilitate cancer diagnosis. To some extent, the performances of deep learning algorithms are similar to, or sometimes even better than, those of humans 12,13 . For analysis of H&E-stained pathology images, deep learning methods have been developed to distinguish tumor regions 14 , detect metastasis 15 , predict mutation status 16 , and classify tumors 17 in breast cancer as well as in other cancers.…”
mentioning
confidence: 94%